Árboles para Ibagué: Especies que fortalecen la Estructura Ecológica Principal (2008)
At first, the article presents Ibague´s tree population in its current condition, including a listing of the most representative native and exotic species found in public urban spaces. After that, the article presents the criteria for selecting species to strengthen the Main Ecological Structure, and then it provides us with those selected and recommended as well as their ecological benefit. As such, the article hereby is a result of the research project «Strengthening the Main Ecological Structure through Identification and Selection of Species for Urban Tree-Planting», conducted in seven Colombian cities between 2006 and 2088.